2012
DOI: 10.1177/0269215511432016
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, multicentre, randomized, double-blind, placebo-controlled trial of onabotulinumtoxinA to treat plantarflexor/invertor overactivity after stroke

Abstract: OnabotulinumtoxinA injection for ankle flexor overactivity after stroke was safe and well tolerated but did not alter local spasticity at 12 weeks; it did reduce spasms and improve gait quality. There were no detectable differences between higher and lower doses. A second injection may be associated with greater change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 31 publications
1
48
0
2
Order By: Relevance
“…It is defined as the inability to dorsiflex the foot beyond the plantigrade level, or neutral. This nonoperative management is often supplemented by treatment aimed at reducing spasticity that can be effectively achieved by a course of botulinum toxin injection to the spastic muscle [13,14]. The midfoot and forefoot are in neutral alignment in equinus deformity.…”
Section: Equinus Deformitymentioning
confidence: 99%
“…It is defined as the inability to dorsiflex the foot beyond the plantigrade level, or neutral. This nonoperative management is often supplemented by treatment aimed at reducing spasticity that can be effectively achieved by a course of botulinum toxin injection to the spastic muscle [13,14]. The midfoot and forefoot are in neutral alignment in equinus deformity.…”
Section: Equinus Deformitymentioning
confidence: 99%
“…BTX-A is also used as an analgesic in migraine, diabetic neuropathic pain, and complex regional pain syndrome (27,28). Dunne et al (29) injected BTX-A (200 or 300 U) into the lower extremities of 85 patients and found a significant decrease in spasticity and pain at the end of 12 weeks. In another study, 500 U BTX-A was injected into the pectoralis major muscle of post-stroke patients for the treatment of spastic shoulder pain and the improvement in pain lasted for 6 months (30).…”
Section: Discussionmentioning
confidence: 99%
“…BoNT has been shown to be effective at decreasing muscle tone in all [54,[66][67][68][69] but one study [70]. Similarly, two studies found improvement in pain [69,70] and increasing range of motion [54,67], respectively, but others found no difference between treatment and placebo groups in measures of pain [67] and range of motion [69] in adults with lower extremity spasticity.…”
Section: Adult Spasticity In the Lower Extremitiesmentioning
confidence: 98%
“…Similarly, two studies found improvement in pain [69,70] and increasing range of motion [54,67], respectively, but others found no difference between treatment and placebo groups in measures of pain [67] and range of motion [69] in adults with lower extremity spasticity. The only study assessing active joint movement, spasm frequency and gait quality found a significant benefit in participants treated with BoNT as opposed to those receiving placebo.…”
Section: Adult Spasticity In the Lower Extremitiesmentioning
confidence: 99%